Efficient resource utilization of the electricity distribution sector using nonparametric data envelopment analysis and influential factors - Ikram, Majid; Rafique, Muhammad Zahid; Mohammed, Kamel Si; Waheed, Rida; Ferraz, Diogo [UNESP] (Elsevier, 2023)
This study aims to investigate the efficient resource utilization of the electricity distribution sector in Pakistan and identifies the influential factors affecting it. In Pakistan, there is excess production capacity and under-utilized power plants, which pose a challenge to the economy due to their burden on the exchequer account and the high power costs. The present study employs the most recent 11 distribution firms panel data from Pakistan for the period 2016–2020 to evaluate the performance ranking of distribution utilities. The study employs standard frontiers, composite indexes, and a novel DEA-windows analysis to measure the efficiency of the distribution utilities. The results of the analysis show that electricity sales, consumer density, and industrial consumers have a positive impact, while distribution losses have a negative association with the efficiency of the distribution utilities. These findings provide valuable insights for policymakers and industry stakeholders in improving the resource utilization and overall performance of the electricity distribution sector. The study highlights the implications of the results in terms of reducing greenhouse gas emissions, which are one of the main contributors to global warming. In conclusion, this study provides an essential contribution to the literature on efficient resource utilization in the electricity distribution sector in Pakistan.
Keywords: Data envelopment analysis; Efficiency analysis; Electricity distribution utilities. external factors; Pakistan; Sustainable policy